PENGARUH KOMPOS LIMBAH SAYURAN TERHADAP BIBIT KARET (Hevea brasiliensis Muell. Arg) PADA TANAH BEKAS TAMBANG EMAS - Tri Ibnu Hajar; Rika Fitry Ramanda; Sarwendah Ratnawati Hermanto (Politeknik Negeri Ketapang, 2025)
The productivity of rubber plants in Indonesia is relatively low, so efforts to increase productivity need to be made, one of which is by improving cultivation technology, the limitation of nutrients in the soil of former gold mines is overcome by providing vegetable waste compost. Vegetable waste compost has a C-organic content of 28.89%, N 1.57%, P 1.39%, K 0.69%. This study aims to determine the effect of vegetable waste compost on the growth of rubber seedlings on the soil of former gold mining land. The research was conducted at the Sukaharja Experiment Garden, Gg. Pandan, from April to July 2024. The study used a non-factorial Complete Random Design (RAL) consisting of 5 groups and 5 replicates, there were 25 experimental units, each experiment consisted of 3 samples so that the total number of samples was 75 samples. The parameters observed were the height of the seedlings, the diameter of the stems, the number of umbrellas, and the dry weight of the seedlings. The data is statistically analyzed with Analysis of Variance (ANOVA), if obtained has a real effect, then the Duncan Multi Range Test (DMRT) is continued at the level of 5%. The results of the fingerprint showed that the treatment of vegetable waste composting had a real influence on the variables of seedling height, stem diameter, number of umbrellas, and root volume. The results of the DMRT test at 5% level show that treatment with a dose of vegetable waste compost of 640 g/polybag is able to provide good growth for the growth of rubber seedlings.